Holocene alluvial sequence in the Val de Zaragoza (Los Monegros) in the paleoenvironmental context of the Ebro Basin (NE Spain) - Peña Monné, José Luis (2018)
Flat-bottomed valleys formed by Holocene fills are the most characteristic landforms in the center of the Ebro basin. This paper analyzes, within a regional framework, a small fluvial basin located in the north of the Alcubierre Range. Three Holocene morphosedimentary units (H1-H3) and a subfunctional level (H4) are identified. These units are representative of the regional geomorphological evolutionary process in the Ebro basin. New chronological insights on climate and landscape management are provided by a study of the Bastarás weir, a construction made for water flow management during the Little Ice Age (LIA). The integration of Val de Zaragoza radiocarbon datings intothe regional framework enables the authors to identify the main formation stages, as well as the influence of climatic and human factors on its evolution. The intensification of human pressure in the territory is reflected in a progressive increase in sediment accumulation rates in the valleys, peaking during Roman times and the Little Ice Age.